O Impacto da cibersegurança na qualidade das demonstrações financeiras - Borges, Gustavo Lima (2024)
The domain of cybersecurity has become increasingly critical in the modern digital era, particularly for financial institutions that protect large amounts of sensitive data and financial resources. This research aims to explore the interplay between cybersecurity practices and the quality of financial disclosures, with a focus on how cybersecurity measures impact the accuracy, transparency and reliability of financial reporting in financial institutions. Using a systematic literature review methodology, the study meticulously analyzes a diverse selection of academic articles and studies to extract significant insights. The results indicate that effective cybersecurity measures positively correlate with the accuracy and completeness of financial disclosures, while cybersecurity incidents negatively impact their transparency and reliability. The finding underscores the need for financial institutions to integrate robust cybersecurity practices to not only protect digital assets but also to improve their competitive position in the financial sector. This study highlights the importance of proactive compliance and technology investments, advocating a comprehensive approach that ensures regulatory adherence and promotes trust and transparency in an increasingly digital financial environment. Future research should focus on the evolving nature of cyber threats and the role of technological innovation in continually improving security and compliance practices.